CORRECTING ERRORS: THE RELATIVE EFFICACY OF DIFFERENT FORMS OF ERROR FEEDBACK IN SECOND LANGUAGE WRITING - Chitra Jayathilake (English Review: Journal of English Education, 2013)
Abstract: Error correction in ESL (English as a Second Language) classes has been a focal phenomenon in SLA (Second Language Acquisition) research due to some controversial research results and diverse feedback practices. This paper presents a study which explored the relative efï¬cacy of three forms of error correction employed in ESL writing classes: focusing on the acquisition of one grammar element both for immediate and delayed language contexts, and collecting data from university undergraduates, this study employed an experimental research design with a pretest-treatment-posttests structure. The research revealed that the degree of success in acquiring L2 (Second Language) grammar through error correction differs according to the form of the correction and to learning contexts. While the ï¬ndings are discussed in relation to the previous literature, this paper concludes creating a cline of error correction forms to be promoted in Sri Lankan L2 writing contexts, particularly in ESL contexts in Universities. Keywords: error correction, written corrective feedback (WCF), English as a second language (ESL), metalinguistic information, second language acquisition (SLA)